Asymmetric Sulfur‐Ylide‐Mediated Formal [4+1]‐Annulation Reaction: Scope and Mechanism. Issue 44 (9th July 2018) - Clergue, Sébastien; Rousseau, Olivier; Delaunay, Thierry; Dequirez, Geoffroy; Tran, Trieu‐Van; El Aakchioui, Soumia; Barozzino‐Consiglio, Gabriella; Robiette, Raphaël
Abstract: A formal [4+1]‐annulation strategy between sulfur ylides and 1, 3‐dienes was developed to afford functionalized cyclopentanoids. The process consists of a stereoselective cyclopropanation reaction followed, in situ, by a stereospecific MgI2 ‐catalyzed vinylcyclopropane–cyclopentene rearrangement. The use of chiral sulfur ylides provided cyclopentanoids with excellent enantiocontrol. A combined experimental and computational mechanistic study showed that the stereospecificity of the rearrangement could be accounted for by a double SN 2 reaction mechanism involving iodide. Abstract : Give me five : A formal [4+1] annulation between sulfur ylides and 1, 1‐bis‐activated 1, 3‐dienes to afford functionalized cyclopentenes has been developed. The reaction shows a good functional group tolerance and a high diastereo‐ and enantiocontrol can be achieved using chiral sulfur ylides. A combined experimental and computational study allowed for a detailed understanding of the mechanism and the origin of stereoselectivity. (HMDS=hexamethyldisilazide).